MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA BALI SISWA KELAS VIII C - I Dewa Ayu Veoni; I Wayan Mandra; I Nyoman Ranem (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT Low student learning motivation in Balinese language learning has become an important issue affecting students’ participation, interest, and persistence in understanding regional languages. This study aimed to analyze students’ learning motivation before and after the implementation of the Project Based Learning model, describe student activities during project-based learning, and examine the effect of the model on improving the learning motivation of class VIII C students at SMP Wisata Sanur in learning Balinese language. This study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of 34 students. Data were collected through learning motivation questionnaires and student activity observation sheets. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and paired sample t-test with the assistance of SPSS version 25.0. The results showed that the average pretest score of students’ learning motivation was 67.74, categorized as low, while the average posttest score increased to 84.29, categorized as high. Student activity during the implementation of Project Based Learning obtained an average score of 86.62 in the high category. The hypothesis testing results showed a Sig. (2-tailed) value of 0.000 < 0.05 with a t-count value of -16.377. Based on these findings, it can be concluded that the Project Based Learning model has a significant and effective effect on improving students’ motivation in learning the Balinese language. ABSTRAK Rendahnya motivasi belajar siswa dalam pembelajaran Bahasa Bali menjadi salah satu permasalahan yang memengaruhi partisipasi, minat, dan ketekunan siswa dalam memahami bahasa daerah. Penelitian ini bertujuan untuk menganalisis tingkat motivasi belajar siswa sebelum dan sesudah penerapan model Project Based Learning, mendeskripsikan aktivitas siswa selama pembelajaran berbasis proyek, serta menguji pengaruh model tersebut terhadap peningkatan motivasi belajar Bahasa Bali siswa kelas VIII C SMP Wisata Sanur. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan quasi experiment berbentuk one group pretest-posttest design. Subjek penelitian berjumlah 34 siswa. Data dikumpulkan melalui angket motivasi belajar dan lembar observasi aktivitas siswa. Analisis data dilakukan menggunakan statistik deskriptif, uji normalitas Shapiro-Wilk, dan paired sample t-test dengan bantuan SPSS versi 25.0. Hasil penelitian menunjukkan bahwa rata-rata motivasi belajar siswa pada pretest sebesar 67,74 berada pada kategori kurang, sedangkan rata-rata posttest meningkat menjadi 84,29 pada kategori tinggi. Aktivitas siswa selama penerapan Project Based Learning memperoleh rata-rata 86,62 dengan kategori tinggi. Hasil uji hipotesis menunjukkan nilai Sig. (2-tailed) sebesar 0,000 < 0,05 dengan nilai t hitung sebesar -16,377. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model Project Based Learning berpengaruh signifikan dan efektif dalam meningkatkan motivasi belajar Bahasa Bali siswa kelas VIII C SMP Wisata Sanur.